A review of vulvar and vaginal cancers in Ibadan, Nigeria (2013)
The objectives of this study are to give an update on the previous studies on vulvar and vaginal cancers from the University College Hospital (UCH), Ibadan, Nigeria, to elucidate any changes in pattern, and to enumerate some of the factors affecting the management of these cancers at the UCH today. All the cases of cancer of the vulva and vagina seen at the UCH between January 1981 and December 2008 were reviewed and re-classified according to the World Health Organization (WHO) histological classification of 2004. The results are as follows: Vaginal and vulvar cancers were the 4th (1.4%) and 5th (1.2%) most common of the 5913 gynecological cancers seen. The mean age was 49.7 years. Squamous cell carcinoma (SCC) was the most common histological type. Notably, vulvar cancer is more common than vaginal cancer in the US and the UK and this opposes our findings. We studied time periods before and after the year 2000, and found vaginal cancer to be more common before and vulvar cancer after the year 2000. We suggest that this may be related to the introduction of the FIGO guidelines in 2000. We conclude that it is important to strictly adhere to the FIGO guidelines in determining the primary site of origin of these cancers in patients with advanced local disease as this distinction has implications for clinical management. The objectives of this study are to give an update on the previous studies on vulvar and vaginal cancers from the University College Hospital (UCH), Ibadan, Nigeria, to elucidate any changes in pattern, and to enumerate some of the factors affecting the management of these cancers at the UCH today. All the cases of cancer of the vulva and vagina seen at the UCH between January 1981 and December 2008 were reviewed and re-classified according to the World Health Organization (WHO) histological classification of 2004. The results are as follows: Vaginal and vulvar cancers were the 4th (1.4%) and 5th (1.2%) most common of the 5913 gynecological cancers seen. The mean age was 49.7 years. Squamous cell carcinoma (SCC) was the most common histological type. Notably, vulvar cancer is more common than vaginal cancer in the US and the UK and this opposes our findings. We studied time periods before and after the year 2000, and found vaginal cancer to be more common before and vulvar cancer after the year 2000. We suggest that this may be related to the introduction of the FIGO guidelines in 2000. We conclude that it is important to strictly adhere to the FIGO guidelines in determining the primary site of origin of these cancers in patients with advanced local disease as this distinction has implications for clinical management.